Dos homens sendo e tornando-se: Tradição e experiência em E. P. Thompson - Cândido, Tyrone Apollo Pontes (2002)
This dissertation has as its theme the concepts of tradition and experience in the work of Edward Palmer Thompson. More specifically, it intends to understand how, from the youth period until the year of publication of (...)